Детекція гена Or5 стійкості до вовчка соняшнику за допомогою SCAR-маркеру RTS05 - Попов, В.М.; Тереняк, Ю.М.; Акініна, Г.Є.; Шарипіна, Я.Ю.; Долгова, Т.А.; Кириченко, В.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The SCAR-marker RTS05 are linked to Or5-gene mapped on 5.6 сМ from it. The aim of this work was investigation of the presence of SCAR-marker RTS05 on various breeding initial material of sunflower. Methods. We studied the presence of RTS05 marker in 37 inbred lines, 29 interspecific hybrids-based samples and 39 varieties of sunflower that created in The Plant Production Institute nd. a. V. Ya. Yuriev. The identification of RTS05 marker we conducted by polymerase chain reaction (PCR). The amplicon of 650 bp size as a result of amplification was indicated about the presence of Or5-gene. In the case of absence Or5-gene in sunflower samples this specific amplicon was not synthesized. Results. The amplicon of 650 bp size was identified in all type of studied sunflower breeding material. The frequency of RTS05-marker in sunflower samples was different. Conclusions The results of our work are suggested possibility to use sunflower samples with identified Or5-gene for creation initial breeding material resistant to broomrape. Keywords: sunflower, broomrape, DNA-markers, Or5-gene.